Preparation method and application of antioxidant MXene-based flowing electrode material capable of realizing efficient capacitance defluorination

By nitrogen doping and cysteine ​​modification on MXene, the existing MXene's poor fluorine removal effect and poor oxidation resistance in capacitance removal are solved, and high-efficiency capacitor fluorine removal and excellent oxidation resistance are achieved.

CN119612709AActive Publication Date: 2025-03-14OCEAN UNIV OF CHINA

Patent Information

Application Number
CN202411933936.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing MXene has problems with poor fluorine removal effect and poor oxidation resistance in capacitance removal, and the traditional fluorine removal electrode materials have low fluorine adsorption capacity, cumbersome preparation, high energy consumption and low recovery rate.

Method used

By nitrogen doping and cysteine ​​modification on MXene, its conductivity and antioxidant properties are improved, coordination bonds and hydrogen bonds are formed, end groups are protected, and adsorption effect on fluoride ions is enhanced.

Benefits of technology

It realizes high-efficiency capacitor fluorine removal, improves the conductivity and oxidation resistance of the MXene electrode, enhances its adsorption capacity and selectivity to fluorine ions, and has a simple preparation method and excellent cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612709A_ABST
    Figure CN119612709A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an antioxidant MXene-based flowing electrode material capable of realizing efficient capacitance defluorination, and belongs to the technical field of water treatment. The preparation method comprises the following steps: sequentially carrying out nitrogen doping and cysteine modification on MXene to obtain the antioxidant MXene-based flowing electrode material capable of realizing efficient capacitance defluorination. The MXene is prepared by a Lewis acid fused salt etching method. According to the method disclosed by the invention, the electrochemical performance of the MXene electrode is effectively improved, the conductivity of the MXene electrode is enhanced, the protection of terminal groups is realized through cysteine modification, and the oxidation resistance of the MXene electrode is improved. The anti-oxidation MXene-based flowing electrode material prepared by the invention has high specific surface area, large pore volume and multiple adsorption sites, and can realize specific efficient adsorption of fluorine ions through ion intercalation and special functional groups at end positions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a preparation method and application of an antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal. Background Art

[0002] Fluoride ions are common pollutants in water bodies. An intake of 0.5 to 1.0 mg / L is essential for dental health. It also stimulates bone cell proliferation, promotes the absorption and utilization of phosphorus and calcium, accelerates bone formation, and prevents symptoms such as osteoporosis and bone cavities. However, excessive intake of fluoride can lead to fluorosis, irreversible demineralization of teeth and bone tissue, and may also cause damage to the kidneys, thyroid, brain, and liver.

[0003] Fluoride is characterized by strong ligand action and small radius, and it is easy to form a large number of different inorganic and organic compounds in plants, soil, air and rocks. Usually, fluoride exists in groundwater and surface water, and its source is mainly the release of fluoride ions in fluoride-containing minerals. Natural activities such as wind, rain, and volcanic eruptions will promote the release of fluoride ions into soil and groundwater, and after years of accumulation, high-fluoride groundwater is eventually formed.

[0004] At present, the main methods for removing fluoride include coagulation and precipitation, electrodialysis, ion exchange, membrane separation and adsorption. At present, conventional methods for removing fluoride ions from water all have certain limitations. Some new processes derived from the above common processes, such as induced crystallization and capacitive deionization (CDI) technology. Capacitive deionization technology, also known as electrosorption technology, uses highly conductive electrode materials as electrodes. Due to its large adsorption capacity, continuous ion removal and high water recovery rate, it has great advantages over traditional adsorption methods. When a mobile electrode is used, only a small voltage is applied between the two collectors of the CDI system. The mobile electrode is pumped to the electrode compartment and flows between the ion exchange membrane and the corresponding collector. The ions in the influent will migrate through the ion exchange membrane, enter the mobile electrode, and finally adsorb onto the suspended carbon material. The CDI device can continuously desalinate high-salinity feed water without the typical discharge step. The key to capacitive deionization technology is the selection of electrode materials. Materials with high conductivity, large specific surface area and specific active sites should be selected.

[0005] Chinese patent document CN113354039A discloses an iron-zirconium co-modified titanium dioxide nanotube electrode and its electrosorption defluorination, the method comprising: 1) pre-treating the titanium substrate, using a purified titanium plate as an anode, using a copper sheet as a counter electrode, using a mixed solution of 0.10-0.20 mol / L NaF and 10-15 wt% H3PO4 as the electrolyte, applying a voltage of 20-25 V, taking out the titanium sheet after the reaction, rinsing it with deionized water and drying it, and obtaining a titanium dioxide nanotube electrode sample; 2) cooling the sample prepared in step 1) after heat treatment to obtain a shaped titanium dioxide nanotube electrode. The heating rate is 3-5°C / min, and after heating to 400°C, the temperature is kept constant for 1 hour; 3) preparing Fe and Zr precursors and coating them evenly on the outer surface of the titanium dioxide nanotube electrode prepared in step 2), and calcining is repeated 8-10 times after coating, and finally obtaining an iron-zirconium co-modified titanium dioxide nanotube electrode. However, the fluorine adsorption capacity of the traditional defluorination electrode material is low, and the electrode preparation is cumbersome, energy consumption is high, and the recovery rate is low. Therefore, it is urgent to develop a new mobile electrode with simple preparation process, high conductivity, environmental friendliness, and reusability, so as to enhance the selective adsorption of fluoride ions in water.

[0006] MXene is a type of two-dimensional transition metal carbide, nitride or carbonitride with excellent electrical conductivity and hydrophilicity. It can form a stable colloidal solution and can now be mass-produced without loss of performance. It has been proposed as a useful environmental remediation material, including heavy metal adsorption, pollutant adsorption and desalination technology, and is an optional mobile electrode material for capacitive defluorination. However, the existing MXene has the problems of poor defluorination effect and poor oxidation resistance in capacitive defluorination. Therefore, if an antioxidant MXene-based mobile electrode material that can achieve efficient capacitive defluorination can be developed, it will have great application prospects. Summary of the invention

[0007] The purpose of the present invention is to provide a preparation method and application of an antioxidant MXene-based mobile electrode material that can achieve efficient capacitive fluorine removal, so as to solve the problems existing in the above-mentioned prior art.

[0008] To achieve the above object, the present invention provides the following solutions:

[0009] One of the technical solutions of the present invention: a method for preparing an antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal, comprising the following steps:

[0010] MXene is sequentially doped with nitrogen and modified with cysteine ​​to obtain the antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal.

[0011] Nitrogen doping can improve the conductivity of MXene. Using cysteine ​​to modify the nitrogen-doped MXene can make the terminal groups on the surface of nitrogen-doped MXene bond with cysteine ​​to form coordination bonds and hydrogen bonds, thereby protecting the terminal groups and preventing MXene from being oxidized by oxygen molecules in water, thereby improving its chemical stability. Nitrogen doping and cysteine ​​modification can effectively improve the adsorption effect of MXene on fluoride ions.

[0012] Furthermore, the nitrogen doping step includes: dispersing the MXene in an ammonium chloride solution, allowing the MXene to stand for colloidal precipitation, aspirating the supernatant, drying the precipitate, and calcining to obtain the nitrogen-doped MXene.

[0013] The above steps attract the positively charged ammonium salt into the gaps between MXene layers through electrostatic attraction to achieve nitrogen doping of MXene.

[0014] Furthermore, the concentration of the ammonium chloride solution is 1.0 to 3.0 mol / L; the dosage ratio of the MXene to the ammonium chloride solution is 1.0 to 2.0 g: 30 mL;

[0015] And / or, the calcination temperature is 450-600° C. and the calcination time is 2-4 hours.

[0016] Furthermore, the standing time is 30 to 90 minutes.

[0017] Furthermore, the calcination is performed under an argon atmosphere.

[0018] Furthermore, after the calcination, the calcined product is further washed and dried, specifically, washed with water for 3 to 5 times, and then dried at 40 to 60° C. for 8 to 10 hours.

[0019] Furthermore, the cysteine ​​modification step includes: mixing the nitrogen-doped MXene and cysteine ​​solution, stirring evenly, adding sodium chloride, and continuing to stir (to ensure that the particles are fully wetted) to obtain the antioxidant MXene-based mobile electrode material that can achieve efficient capacitive fluoride removal.

[0020] Furthermore, the concentration of the cysteine ​​solution is 0.05-1.0 mol / L; the usage ratio of the nitrogen-doped MXene to the cysteine ​​solution and sodium chloride is 100-250 mg:30 mL:15-45 mg.

[0021] Furthermore, the stirring time after mixing the nitrogen-doped MXene and the cysteine ​​solution is 1 to 5 hours; and the stirring time after adding the sodium chloride is 12 to 24 hours.

[0022] Furthermore, the stirring speed is 50-100 r / min.

[0023] Furthermore, the MXene is prepared by a Lewis acid molten salt etching method, and the preparation steps include: mixing a MAX precursor with copper chloride, potassium chloride and sodium chloride to obtain a mixed solid powder; soaking the mixed solid powder in anhydrous ethanol and then calcining to obtain the MXene.

[0024] MXene prepared by the fluorine-free method through Lewis acid molten salt etching has a large number of terminal groups (Cl-, OH-, etc.) on its surface. After mixing with ammonium chloride solution, more nitrogen can enter between MXene layers through electrostatic attraction with positively charged ammonium ions.

[0025] Further, the molar ratio of the MAX precursor to copper chloride (CuCl2), potassium chloride (NaCl) and sodium chloride (KCl) is 1:3:2:2;

[0026] And / or, the calcination temperature is 700-750° C. and the calcination time is 8-12 hours.

[0027] Furthermore, the MAX precursor is Ti3AlC2.

[0028] Furthermore, the usage ratio of the mixed solid powder to the anhydrous ethanol is 5g:10-20mL.

[0029] Furthermore, the soaking is carried out under vacuum conditions at 25 to 30° C., and the soaking time is 12 to 24 hours.

[0030] Furthermore, the calcination is performed under an argon atmosphere.

[0031] Furthermore, after the calcination, the calcined product is also washed and dried, specifically: first washed with water for 3 to 5 times (to remove unreacted substances), then washed with 0.1 mol / L ammonium persulfate solution for 3 to 5 times (to remove the copper element replaced by the molten salt), then washed with ethanol and pure water for 3 times each, and finally vacuum dried at 25 to 30°C for 12 to 24 hours.

[0032] The second technical solution of the present invention: an antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal obtained according to the above-mentioned preparation method.

[0033] The third technical solution of the present invention: Application of the above-mentioned antioxidant MXene-based mobile electrode material that can achieve efficient capacitive fluorine removal in capacitive fluorine removal.

[0034] Furthermore, the application in capacitive defluorination specifically refers to applying the antioxidant MXene-based mobile electrode material to capacitive deionization to remove fluoride ions in water.

[0035] The present invention first adopts a fluorine-free method to prepare MXene with rich terminal groups by Lewis acid molten salt etching, and then mixes it with ammonium chloride, and introduces ammonium ions into the gaps between MXene levels by electrostatic attraction with positively charged ammonium ions to achieve nitrogen doping, thereby enhancing the conductivity of MXene. Then, by bonding with cysteine, coordination bonds and hydrogen bonds are formed to protect the terminal groups on the surface of MXene, prevent MXene from being oxidized by oxygen molecules in water, and improve its chemical stability. The method of the present invention effectively improves the electrochemical properties of the MXene electrode, enhances its conductivity, and protects the terminal groups by cysteine ​​modification, thereby improving its antioxidant properties. The antioxidant MXene-based mobile electrode material prepared by the present invention has a high specific surface area, a large pore volume and multiple adsorption sites, and can achieve specific and efficient adsorption of fluoride ions through ion intercalation and special functional groups on the terminal positions.

[0036] The preparation method of the present invention is simple, and the obtained antioxidant MXene-based mobile electrode material has a high adsorption capacity for fluoride ions, can be used in capacitive deionization technology to achieve efficient removal of fluoride ions in water, has great advantages over traditional methods, and is suitable for industrial preparation and for the treatment of actual fluoride-containing wastewater.

[0037] The present invention discloses the following technical effects:

[0038] (1) The present invention improves the conductivity of MXene electrode materials by nitrogen doping MXene, and protects the surface end groups of MXene from oxidation through the bonding action of cysteine, thereby improving its chemical stability, and finally obtaining a mobile electrode material with high conductivity and excellent adsorption performance for fluoride ions.

[0039] (2) The antioxidant MXene-based mobile electrode material of the present invention is based on the ion exchange between fluoride ions and the terminal groups on the surface of the NCMT electrode, and the fluoride ions are electrostatically attracted to the space between the MXene sheets through the functional groups on both sides of the terminal and the redox reaction of the titanium atoms in the MXene nanosheets to remove fluoride ions from the water. Compared with the traditional capacitive deionization method, the adsorption capacity is greatly improved.

[0040] (3) The antioxidant MXene-based mobile electrode material prepared by the present invention has excellent cycle performance and can still achieve a high fluorine removal efficiency after multiple cycles. There is no secondary pollution during the treatment process, which is safe, environmentally friendly and has low energy consumption.

[0041] (4) The antioxidant MXene-based mobile electrode material of the present invention has good ion selectivity and has a high selectivity for removing fluoride ions, and has no significant effect on other common anions in water within the range of drinking water.

[0042] (5) The antioxidant MXene-based mobile electrode material of the present invention was compared before and after use and found that the electrode had little mass loss, was non-toxic, had no secondary pollution problems, and the water quality after treatment met the standards and was safe and reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 The SEM image of the antioxidant MXene-based electrode material (0.5NCMT) prepared in Example 1 that can achieve efficient capacitive fluorine removal, wherein (A) and (B) are images at different magnifications, respectively;

[0045] Figure 2 Infrared spectra of different types of MXene-based mobile electrode materials prepared in Example 1 and Comparative Examples 1-2;

[0046] Figure 3 Capacitive defluorination curves of different types of MXene-based mobile electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2;

[0047] Figure 4 Capacitive fluoride removal curve of the antioxidant MXene-based mobile electrode material (0.5NCMT) prepared in Example 1 under fluoride ion solution conditions with different initial concentrations;

[0048] Figure 5 Capacitive defluorination curve of the antioxidant MXene-based mobile electrode material (0.5NCMT) prepared in Example 1 under the coexistence of different types of interfering ions;

[0049] Figure 6 Capacitive defluorination curve of the antioxidant MXene-based mobile electrode material (0.5NCMT) prepared in Example 1 under different flow rate conditions;

[0050] Figure 7 Capacitive fluorine removal curves of the antioxidant MXene-based mobile electrode material (0.5NCMT) prepared in Example 1 at different applied voltages;

[0051] Figure 8 This is a graph showing the adsorption performance of fluoride ions after multiple cycles of the antioxidant MXene-based mobile electrode material (0.5NCMT) prepared in Example 1;

[0052] Fig. 9This is a SEM image of the antioxidant MXene-based electrode material (0.5NCMT) prepared in Example 1 that can achieve efficient capacitive fluorine removal after multiple adsorptions;

[0053] Fig.10 These are the antioxidant test images of different types of MXene-based mobile electrode materials prepared in Example 1 and Comparative Examples 1-2 that change over time in aqueous solution. DETAILED DESCRIPTION

[0054] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0055] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0056] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0057] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0058] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0059] As a first aspect of the present invention, the present invention provides a method for preparing an antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal, comprising the following steps:

[0060] MXene is sequentially doped with nitrogen and modified with cysteine ​​to obtain the antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal.

[0061] As a preferred embodiment of the present invention, the preparation method more specifically comprises the following steps:

[0062] (1) Preparation of MXene by Lewis acid molten salt etching method: MAX precursor (Ti3AlC2) was mixed with copper chloride, potassium chloride and sodium chloride to obtain a mixed solid powder; the mixed solid powder was soaked in anhydrous ethanol and then calcined to obtain the MXene (denoted as MS-Ti3C2T x );

[0063] (2) Nitrogen doping: The MXene is dispersed in an ammonium chloride solution, and after standing for colloidal precipitation, the supernatant is sucked out, and the precipitate is dried and calcined to obtain nitrogen-doped MXene (denoted as N / MS-Ti3C2T x );

[0064] (3) Cysteine ​​modification: The nitrogen-doped MXene and cysteine ​​solution were mixed, stirred evenly, and then sodium chloride was added and stirred continuously to obtain the antioxidant MXene-based mobile electrode material (denoted as N-Cys / MS-Ti3C2T x ).

[0065] As a preferred embodiment of the present invention, in step (1):

[0066] The molar ratio of the MAX precursor to copper chloride, potassium chloride and sodium chloride is 1:3:2:2;

[0067] The calcination temperature is 700-750°C and the calcination time is 8-12h;

[0068] The ratio of the mixed solid powder to the anhydrous ethanol is 5 g:10-20 mL;

[0069] The soaking is carried out under vacuum conditions at 25 to 30° C., and the soaking time is 12 to 24 hours;

[0070] The calcination is carried out under an argon atmosphere;

[0071] After the calcination, the calcined product is also washed and dried, specifically: first washed with water for 3 to 5 times (to remove unreacted substances), then washed with 0.1 mol / L ammonium persulfate solution for 3 to 5 times (to remove the copper element replaced by the molten salt), then washed with ethanol and pure water for 3 times each, and finally vacuum dried at 25 to 30° C. for 12 to 24 hours.

[0072] As a preferred embodiment of the present invention, in step (2):

[0073] The concentration of the ammonium chloride solution is 1.0-3.0 mol / L; the dosage ratio of the MXene to the ammonium chloride solution is 1.0-2.0 g:30 mL;

[0074] The calcination temperature is 450-600°C and the calcination time is 2-4h;

[0075] The standing time is 30 min;

[0076] The calcination is carried out under an argon atmosphere;

[0077] After the calcination, the calcined product is further washed and dried, specifically: washed with water for 3 to 5 times, and then dried at 40 to 60° C. for 8 to 10 hours;

[0078] As a preferred embodiment of the present invention, in step (3):

[0079] The concentration of the cysteine ​​solution is 0.05-0.20 mol / L; the usage ratio of the nitrogen-doped MXene to the cysteine ​​solution and sodium chloride is 100-250 mg:30 mL:15-45 mg.

[0080] The stirring time after mixing the nitrogen-doped MXene and the cysteine ​​solution is 1 hour; the stirring time after adding the sodium chloride is 10 to 12 hours.

[0081] The stirring speed is 50-100 r / min.

[0082] As a second aspect of the present invention: The present invention provides an antioxidant MXene-based mobile electrode material that can achieve efficient capacitive fluorine removal, which is prepared according to the above-mentioned preparation method.

[0083] As the third aspect of the present invention: the present invention provides the application of the above-mentioned antioxidant MXene-based mobile electrode material that can achieve efficient capacitive fluorine removal in capacitive fluorine removal.

[0084] The preparation method and application of the antioxidant MXene-based flow electrode of the present invention are further described below in conjunction with specific embodiments.

[0085] All raw materials used in the following examples and comparative examples are common commercially available products.

[0086] Example 1

[0087] An antioxidant MXene-based mobile electrode material (N-Cys / MS-Ti3C2T4) for efficient capacitive fluoride removal x , referred to as NCMT), the steps are as follows:

[0088] (1) Preparation of MXene by Lewis acid molten salt etching: 1.125g MAX precursor (Ti3AlC2) and 2.380g copper chloride were mixed and added to an agate mortar and ground for 10 minutes. Then 0.865g potassium chloride and 0.675g sodium chloride were added to the agate mortar and ground for 20 minutes to obtain a mixed solid powder. Among them, the molar ratio of the four solid materials was 1:3:2:2. Then, the mixed solid powder was poured into a 10×12cm corundum crucible, flattened, and 10mL of anhydrous ethanol was added to immerse the mixed solid powder, and the corundum crucible was soaked at 30°C for 24h under vacuum conditions. After soaking, it was calcined at 700°C for 10h in an argon atmosphere with a heating rate of 5°C / min. After cooling, the solid material was ground for 10 min, washed with pure water for 3 times to remove unreacted substances, and then washed with 0.1 mol / L ammonium persulfate solution for 5 times to remove the copper element replaced by the molten salt, and then washed with ethanol and pure water for 3 times each, and finally centrifuged. The solid material was dried at 25 ° C for 24 h under vacuum conditions to obtain MS-Ti3C2T x .

[0089] (2) Nitrogen doping: 2.0 g MS-Ti3C2T x Add to 30mL 1.5mol / L ammonium chloride solution, let stand for 30min, colloidal precipitation occurs, carefully aspirate the supernatant, dry the remaining precipitate under vacuum at room temperature for 24h, transfer it to a 5×6cm corundum crucible, and calcine at 600℃ for 4h under argon atmosphere with a heating rate of 5℃ / min. After cooling, grind the obtained solid material for 5min and wash it with pure water 5 times to remove unreacted impurities, and finally centrifuge and dry the obtained solid material at 40℃ for 10h under vacuum conditions to obtain N / MS-Ti3C2T x .

[0090] (3) Cysteine ​​modification: 250 mg N / MS-Ti3C2T x Add it into 30mL of 0.5mol / L cysteine ​​solution, stir it at 100r / min for 1h at room temperature, then add 30mg of sodium chloride as electrolyte, and continue stirring for 24h to ensure that the particles are fully wetted to obtain 0.5NCMT of mobile electrode material.

[0091] Example 2

[0092] The same as Example 1, except that the 30 mL 0.5 mol / L cysteine ​​solution in step (3) is replaced with 30 mL 0.2 mol / L cysteine ​​solution to obtain 0.2 N CMT of mobile electrode material.

[0093] Example 3

[0094] The same as Example 1, except that the 30 mL 0.5 mol / L cysteine ​​solution in step (3) is replaced with 30 mL 1.0 mol / L cysteine ​​solution to obtain 1.0 N CMT of mobile electrode material.

[0095] Comparative Example 1

[0096] The same as Example 1, except that the nitrogen doping in step (2) and the cysteine ​​modification in step (3) are not performed, and the MXene obtained by the Lewis acid molten salt etching in step (1), i.e., MS-Ti3C2T x As mobile electrode material.

[0097] Comparative Example 2

[0098] The same as Example 1, except that the cysteine ​​modification in step (3) is not performed, and the MXene-based electrode material after nitrogen doping obtained in step (2), i.e., N / MS-Ti3C2T x As mobile electrode material.

[0099] Comparative Example 3

[0100] The same as Example 1, except that the nitrogen doping in step (2) is not performed, and 2.0 g of MS-Ti3C2T3 obtained by the Lewis acid molten salt method in step (1) is directly taken. x The cysteine ​​modification of step (3) was performed to obtain Cys / MS-Ti3C2T x (abbreviated as CMT) as the mobile electrode material.

[0101] Test Example 1

[0102] Characterization of flow electrode materials

[0103] Figure 1 The SEM image of the antioxidant MXene-based electrode material (0.5NCMT) prepared in Example 1 for achieving efficient capacitive fluorine removal, wherein (A) and (B) are images at different magnifications, respectively. Figure 1 It can be seen that the prepared 0.5NCMT electrode material presents a multilayer accordion structure of typical MXene materials, with a large interlayer spacing and a two-dimensional layer structure. After magnification, it can be clearly observed that cysteine ​​particles are x The material surface is uniformly doped, proving that 0.5NCMT was successfully prepared.

[0104] Figure 2 The infrared spectra of the flow electrode materials prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 2It can be seen that MS-Ti3C2T x Material at 1398cm -1 The Ti-O peak was observed at 3100 cm -1 The OH peak was observed at x MXene was successfully prepared; after nitrogen doping, it can be clearly seen at 3400cm -1 A sharp NH peak was observed at 990 cm -1 The N-Ti peak was observed at x The preparation was successful; after the composite cysteine ​​particles were added, -1 A Ti-S peak was observed at , indicating that the Ti atoms in MXene coordinated with the S atoms in cysteine, proving that the NCMT electrode material was successfully prepared.

[0105] Application Example 1

[0106] This application example is used to examine the performance of the mobile electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 in the field of capacitive fluorine removal. The specific process and results are as follows:

[0107] 30±0.2mL of flowing electrode material was used as the electrode in the FCDI system, the peristaltic pump was controlled to adjust the electrode material flow rate to 40mL / min, and a constant voltage of 1.2V was applied between the graphite current collectors to form an electrosorption defluorination component. 10mg / L sodium fluoride aqueous solution (in F-) was used as simulated wastewater, the treatment volume was 50mL, and the flow was carried out in a 100mL beaker to obtain the capacitive defluorination data of the flowing electrode material, as shown in Figure 3 As shown. Analysis shows that MS-Ti3C2T x 、N / MS-Ti3C2T x The removal efficiency of fluoride ions by CMT, 0.2NCMT, 0.5NCMT and 1.0NCMT at 60 min is significantly higher than that of CMT, MS-Ti3C2T x and N / MS-Ti3C2T x The fluorine removal efficiencies of 0.2NCMT, 0.5MTPA and 1.0NCMT were all below 90% (61.5, 66.4 and 88.5% respectively), which did not reach the acceptable level of the national standard (<1.0mg / L). The fluorine removal efficiencies of 0.2NCMT, 0.5MTPA and 1.0NCMT were 92.6%, 98.1% and 94.3% respectively, which successfully removed the conventional concentration of fluorine-containing wastewater to below the national standard. This shows that after nitrogen doping + cysteine ​​modification, the appropriate loading amount can greatly improve the fluoride ion adsorption capacity of MXene, and it has the potential for practical application in removing fluoride ions from water.

[0108] Application Example 2

[0109] This application example is used to investigate the capacitive fluoride removal performance of the antioxidant MXene-based mobile electrode material prepared in Example 1 under fluoride ion solution conditions with different initial concentrations. The specific process and results are as follows:

[0110] 30±0.2mL of flowing electrode material was used as the electrode in the FCDI system, and the peristaltic pump was controlled to adjust the flow rate of the flowing electrode material to 40mL / min. A constant voltage of 1.2V was applied between the graphite current collectors to form an electro-adsorption defluorination component. Capacitive defluorination was performed using 5, 10, 30, 50, and 100mg / L sodium fluoride aqueous solution (in terms of F-) as simulated wastewater, with a treatment volume of 50mL in a 100mL beaker. The capacitive defluorination data of the flowing electrode material were obtained, as shown in Figure 2. Figure 4 As shown, the sodium fluoride aqueous solution with initial concentrations of 5, 10, 30, 50, and 100 mg / L was electrosorbed for 120 minutes and then removed to 0.15, 0.32, 5.33, 13.56, and 22.27 mg / L, respectively. This shows that the 0.5NCMT electrode prepared in Example 1 can achieve short-term and efficient removal of fluoride ions in aqueous solution and has a wide concentration gradient application range.

[0111] Application Example 3

[0112] This application example is used to investigate the capacitive fluorine removal performance of the antioxidant MXene-based mobile electrode material prepared in Example 1 under different types of interfering ions. The specific process and results are as follows:

[0113] 30±0.2mL of flowing electrode material was used as the electrode in the FCDI system, the peristaltic pump was controlled to adjust the flow rate of the flowing electrode material to 40mL / min, and a constant voltage of 1.2V was applied between the graphite collector plates to form an electrosorption defluorination component. - The simulated wastewater was added with different types of interfering ions (Cl-, NO3 - 、SO4 2- PO4 3- ), with a processing volume of 50 mL, was carried out in a 100 mL beaker to obtain capacitive defluorination data of the flow electrode material, such as Figure 5 As shown. When the concentration of interfering ions and fluoride ions is the same, even PO4 3- Under the coexistence conditions, the removal efficiency of fluoride ions by the 0.5NCMT flow electrode can still reach more than 50%, and the Cl - Under the coexistence conditions, the removal efficiency of fluoride ions by the NCMT electrode can even reach 80%, proving that the NCMT electrode has excellent selective fluoride ion removal performance.

[0114] Application Example 4

[0115] This application example is used to investigate the capacitive fluorine removal performance of the antioxidant MXene-based flow electrode material prepared in Example 1 under different flow rate conditions. The specific process and results are as follows:

[0116] 30±0.2mL of flowing electrode material was used as the electrode in the FCDI system, and a constant voltage of 1.2V was applied between the graphite current collectors to form an electrosorption defluorination component. - The peristaltic pump was used to adjust the flow rate of the flowing electrode material to 20, 30, 40, 50, and 60 mL / min to simulate wastewater for capacitive defluorination. Multiple experiments were conducted in a 100 mL beaker with a simulated wastewater treatment volume of 50 mL. The capacitive defluorination data of the flowing electrode material were obtained, as shown in Figure 2. Figure 6 As shown in the figure, in the flow rate range of 20-40mL / min, as the flow rate increases, the fluoride ion removal efficiency gradually increases. However, as the test flow rate exceeds 40mL / min, the fluoride ion removal efficiency decreases instead of increasing. Considering the energy consumption and fluoride removal efficiency, 40mL / min is selected as the optimal flow rate for the 0.5NCMT flow electrode.

[0117] Application Example 5

[0118] This application example is used to investigate the capacitive fluorine removal performance of the antioxidant MXene-based mobile electrode material prepared in Example 1 under different applied voltages. The specific process and results are as follows:

[0119] 30±0.2mL of flowing electrode material was used as the electrode in the FCDI system, the peristaltic pump was controlled to adjust the flow rate of the flowing electrode material to 40mL / min, and a constant voltage was applied between the graphite collector plates to form an electrosorption defluorination component. - The capacitive defluorination of the simulated wastewater was carried out by applying constant voltages of 0.4, 0.8, 1.0, 1.2 and 1.6 V between the graphite collector plates. Multiple groups of experiments were carried out. The simulated wastewater treatment volume was 50 mL. The experiments were carried out in a 100 mL beaker. The capacitive defluorination data of the flow electrode material were obtained, such as Figure 7As shown. When the voltages were 0.4, 0.8, 1.0, 1.2 and 1.6 V, the 0.5 N CMT flow electrode could remove the sodium fluoride aqueous solution with an initial concentration of 10 mg / L to 4.65, 3.45, 2.34, 0.74 and 0.45 mg / L within 60 min. It can be seen that with the increase of the applied voltage, the removal capacity of the NCMT flow motor gradually increases. Considering that the fluoride ion concentration can be removed to below 1.0 mg / L (acceptable level) when the applied voltage is 1.2 V and 1.6 V, and the energy consumption is lower when the applied voltage is 1.2 V, 1.2 V is selected as the optimal operating voltage of the 0.5 N CMT flow electrode.

[0120] Application Example 6

[0121] This application example is used to investigate the capacitive fluorine removal performance of the antioxidant MXene-based flow electrode material prepared in Example 1 in multiple cycle experiments. The specific process and results are as follows:

[0122] 30±0.2mL of flowing electrode material was used as the electrode in the FCDI system, the peristaltic pump was controlled to adjust the flow rate of the flowing electrode material to 40mL / min, and a constant voltage of 1.2V was applied between the graphite collector plates to form an electrosorption defluorination component. - After the first capacitive defluorination experiment was completed, the circulating water in the FCDI system was drained and then re-applied with new simulated fluoride-containing wastewater of equal concentration as the next cycle of electro-adsorption defluorination. The results are shown in the figure. Figure 8 After 20 cycles of defluorination experiments, the 0.5N CMT flow electrode still has a high removal efficiency, which remains above 85%, proving that the 0.5N CMT flow electrode has excellent cyclic defluorination performance and chemical stability.

[0123] Fig. 9 This is a SEM image of the antioxidant MXene-based electrode material prepared in Example 1 after multiple (20 cycles) adsorption. Fig. 9 It can be seen that the 0.5NCMT mobile electrode still has a two-dimensional layer structure and is complete in structure, indicating that it has chemical stability and antioxidant properties in aqueous solution, and has good recycling performance when used for capacitor defluorination.

[0124] Test Example 2

[0125] Antioxidation performance test of mobile electrode materials

[0126] Fig.10The antioxidant test images of different types of MXene-based mobile electrode materials prepared in Example 1 and Comparative Examples 1-2 in aqueous solution over time, the concentration of the electrode material in the aqueous solution is 0.1 mg / L, and the test temperature is 25°C. Fig.10 It can be seen that the MS-Ti3C2T x After only 60 days of storage in water, the solution gradually became transparent, indicating that pure MS-Ti3C2T x Does not have antioxidant ability; N / MS-Ti3C2T in Comparative Example 2 x After being stored in water for 120 days, the solution was mostly transparent, indicating that N / MS-Ti3C2T x Most of it has been oxidized; while the 0.5N CMT in Example 1 was stored in water for 120 days, and the solution was still dark black, indicating that 0.5N CMT exhibited good chemical stability.

[0127] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal, characterized in that: The following steps are involved: MXene is sequentially doped with nitrogen and modified with cysteine ​​to obtain the antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal.

2. The preparation method according to claim 1, characterized in that The nitrogen doping step includes: dispersing the MXene in an ammonium chloride solution, allowing the MXene to stand for colloidal precipitation, sucking out the supernatant, drying the precipitate, and calcining to obtain the nitrogen-doped MXene.

3. The preparation method according to claim 2, characterized in that: The concentration of the ammonium chloride solution is 1.0-3.0 mol / L; the dosage ratio of the MXene to the ammonium chloride solution is 1.0-2.0 g:30 mL; And / or, the calcination temperature is 450-600° C. and the calcination time is 2-4 hours.

4. The preparation method according to claim 2, characterized in that: The cysteine ​​modification step includes: mixing the nitrogen-doped MXene and cysteine ​​solution, stirring evenly, adding sodium chloride, and continuing to stir to obtain the antioxidant MXene-based mobile electrode material that can achieve efficient capacitive fluoride removal.

5. The preparation method according to claim 4, characterized in that: The concentration of the cysteine ​​solution is 0.05-1.0 mol / L; the usage ratio of the nitrogen-doped MXene to the cysteine ​​solution and sodium chloride is 100-250 mg:30 mL:15-45 mg.

6. The preparation method according to claim 4, characterized in that: The stirring time after mixing the nitrogen-doped MXene and the cysteine ​​solution is 1 to 5 hours; the stirring time after adding the sodium chloride is 12 to 24 hours.

7. The preparation method according to claim 1, characterized in that: The MXene is prepared by a Lewis acid molten salt etching method, and the preparation steps include: mixing a MAX precursor with copper chloride, potassium chloride and sodium chloride to obtain a mixed solid powder; soaking the mixed solid powder in anhydrous ethanol and then calcining to obtain the MXene.

8. The preparation method according to claim 1, characterized in that: The molar ratio of the MAX precursor to copper chloride, potassium chloride and sodium chloride is 1:3:2:2; And / or, the calcination temperature is 700-750° C. and the calcination time is 8-12 hours.

9. An antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal, obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the antioxidant MXene-based mobile electrode material capable of achieving efficient capacitive fluorine removal as claimed in claim 9 in capacitive fluorine removal.

Citation Information

Patent Citations

  • Iron-zirconium co-modified titanium dioxide nanotube electrode and electro-adsorption defluorination method thereof

    CN113354039A

  • A lithium iron phosphate composite cathode material and a preparation method thereof

    CN109004207A

  • Preparation method of anion-doped cobalt-based photo-anode material

    CN110902777A

  • Ti3C2MXene material prepared based on molten salt method at low cost and preparation method of Ti3C2MXene material

    CN116119668A

  • Method for preparing Cys (at) MgAlCe-LDH / WPU self-repairing anti-corrosion coating

    CN117887343A

Cited By

  • Hydrophobic Ti3C2Tx and application thereof in deionized water treatment of membrane-free capacitor

    CN120346687A

  • Directional design and screening method for nitrogen doping-organic group coordinated regulation and control of MXene non-noble metal hydrogen evolution electrocatalyst

    CN121565302A